Unraveling the Effect of A-Site Sr-Doping in Double Perovskites Ca2-xSrxScRuO6 (x=0 and 1): Structural Interpretation and Mechanistic Investigations of Trifunctional Electrocatalytic Effects - Kumar, Nikhil; Rom, Tanmay; Kumar, Mukesh; Nagaiah, Tharamani C.; Lee, Eoyoon; Ham, Hyung Chul; Choi, Sun Hee; Rayaprol, Sudhindra; Siruguri, Vasudeva; Mandal, Tapas Kumar; Kennedy, Brendan J.; Paul, Avijit Kumar (AMER CHEMICAL SOC, 2022)
Toward the development of sustainable and clean energy sources for the replacement of fossil fuels, strategies for constructing highly effective and durable trifunctional oxide electrocatalysts with zero emission carbon is a key step for boosting energy technologies through overall water splitting, regenerative fuel cells, and metal-air batteries. Here, two disordered ruthenate double-perovskites Ca2ScRuO6 (CSR) and CaSrScRuO6 (CSSR) were synthesized by the conventional high-temperature solid-state reaction method, and their trifunctional electrocatalytic behaviors for the oxygen reduction reaction (ORR) and oxygen and hydrogen evolution reactions (OER/HER) were investigated in alkaline medium (1 M KOH). The orthorhombic (space group Pbnm) crystal structures of both CSR and CSSR were refined from the neutron and laboratory X-ray powder diffraction data. The oxidation states of Ru cations in both compounds were shown to be predominantly Ru+5, confirmed by X-ray photoelectron spectroscopy studies. The as-prepared bulk perovskites showed excellent ORR performance with an onset potential of similar to 0.89 V for CSR and 0.90 V vs reversible hydrogen electrode (RHE) for CSSR, respectively. In addition, both compounds showed significantly low overpotentials toward OER (353 and 323 mV) and HER (313 and 275 mV) at a current density of 10 mA cm(-2), demonstrating them to be active trifunctional electrocatalysts. The substitution of an alkaline earth metal at the A-site introduces a synergistic effect of structural distortion and electronic properties of Ru+5 metal ions responsible for enhanced trifunctional electrocatalytic activities. Such trifunctional catalytic behaviors of CSR and CSSR materials can be further understood by density functional theory (DFT) calculations. The present finding not only provides insight into the catalytic activity of these materials but also presents an example of efficient trifunctional bulk-phase oxide electrocatalysts for practical applications.